The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15448/1980-6523.2014.2.13022
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and self-perceived need for complete denture use or exchange

Abstract: Objective: To analyze self-perceived need for complete denture use or replacement in the population aged 35-44 and 65-74 years, as well as to carry out the association between that self-assessment and social capital in the municipalities of Conde and Pedras de Fogo, Paraíba. Methods: A total of 134 adults and 54 elderlies participated in this sectional study. The outcome of interest was self-perceived need for complete denture use or replacement. Data were analyzed descriptively and association between variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The role of social determinants and contextual variables as potential factors influencing oral health have been studied; however, there is no consensus in literature regarding these factors [11,12]. A recent study, including data from the European Union and Israel, showed that the tooth retention in older adults may be related to socioeconomic status in early life, living conditions in childhood, and experiences in oral health throughout life [13].…”
Section: Introductionmentioning
confidence: 99%
“…The role of social determinants and contextual variables as potential factors influencing oral health have been studied; however, there is no consensus in literature regarding these factors [11,12]. A recent study, including data from the European Union and Israel, showed that the tooth retention in older adults may be related to socioeconomic status in early life, living conditions in childhood, and experiences in oral health throughout life [13].…”
Section: Introductionmentioning
confidence: 99%